2020
DOI: 10.3390/ijerph17238945
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Practices and Barriers to Adherence to Healthy Eating among King Faisal University Students

Abstract: Proper dietary practices should be developed during the student years that will continue into the future. This study aimed to identify the eating habits and dietary practices among King Faisal University (KFU) students, explore the barriers to adherence to healthy eating, associate the understanding of healthy diets with students’ characteristics, and determine the association between body mass index (BMI) and awareness of the concept of healthy diets, academic discipline, and enrollment in a nutrition course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
16
0
3
Order By: Relevance
“…Our results were in line with other similar studies in this aspect—low consumption of vegetables and fruits (26.2%) and a high consumption of fast food. [ 6 10 11 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results were in line with other similar studies in this aspect—low consumption of vegetables and fruits (26.2%) and a high consumption of fast food. [ 6 10 11 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in concordance with other studies which identified lack of exercise as one of the common barriers to obesity. [ 10 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer utilization time was significantly predicted to increase skinfolds in boys and girls and BMI in girls alone. 20 Body fatness did not predict any variation in screen time. 21 Other studies also indicated that the frequency of meal intake contributed to the development of obesity.…”
Section: Introductionmentioning
confidence: 87%
“…They indicated their belief that cooking a healthy meal is time-consuming, requires more effort, and costs more than buying fast food or ready-to-eat food. Students also commented that unhealthy and processed food was easily accessible on their university campus, through vending machines or stores [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%